2020
DOI: 10.4103/jpbs.jpbs_53_20
|View full text |Cite
|
Sign up to set email alerts
|

Dental caries and its association with body mass index among school children of Riyadh, Saudi Arabia

Abstract: A BSTRACT Background: Few studies have investigated the relationship of dental caries with obesity among Saudi Arabian population. Hence, this study was conducted to assess the association of obesity with dental caries among school children. Materials and Methods: A cross-sectional, descriptive study was conducted among 12- and 15-year-old government school children of Riyadh. A total of 2247 children were examined from 24 schools of Riyadh. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…Another notable finding is that individuals with higher BMI visit PHC centers less frequently. This pattern warrants further research into the impact of oral health on overall wellbeing, as it aligns with previous studies highlighting a lack of awareness of preventive dental practices among those with high BMI ( Abdellatif and Hebbal, 2020 ; Crocombe et al, 2012 ). Addressing this gap can potentially encourage routine oral health check-ups.…”
Section: Discussionsupporting
confidence: 86%
“…Another notable finding is that individuals with higher BMI visit PHC centers less frequently. This pattern warrants further research into the impact of oral health on overall wellbeing, as it aligns with previous studies highlighting a lack of awareness of preventive dental practices among those with high BMI ( Abdellatif and Hebbal, 2020 ; Crocombe et al, 2012 ). Addressing this gap can potentially encourage routine oral health check-ups.…”
Section: Discussionsupporting
confidence: 86%
“…Conversely, some studies reported that overweight/obese children had lower caries scores [ 13 , 14 , 15 ] or were less likely to have dental caries [ 14 , 16 , 17 , 18 , 19 , 20 , 21 ] compared to children of normal weight. Furthermore, results from several studies indicated that there was no significant association between weight status and caries scores [ 22 , 23 , 24 , 25 ] or caries prevalence [ 22 , 24 , 25 , 26 ]. Several systematic reviews of the childhood obesity-caries relationship indicated that various confounding factors were not evaluated in several previous studies and might affect the findings [ 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study of the selected age group of 6-12 years, it was found that there is a female preference for increased BMI. The prevalence of increasing weight and dental caries in children is a concern in Saudi Arabia [27][28][29][30][31][32]. Alshihri et al [33] reported that obesity and dental caries are multifactorial diseases, and the establishment of an association between these two diseases is very complex.…”
Section: Discussionmentioning
confidence: 99%